AUGMENTATION RHINOPLASTY: 9TH COSTAL CARTILAGE GRAFT FOR STAGE III SADDLE NOSE DEFORMITY: Augmentation Rhinoplasty - Javaid, Rana Hassan; Ali, Shaukat; Kiani, Asma Afzal (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the results of 9th rib costal cartilage in the reconstruction of stage III saddle nose deformity. Study Design: Case series. Place and Duration of Study: Combined Military Hospital Rawalpindi, from Dec 2014 to Jun 2017. Material and Methods: Individuals with stage III saddle nose deformity for at least two years due to trauma or as a sequel of septal surgery, with no history of anxiolytic and antidepressant intake were included in the study. Patient satisfaction level before and after surgery in terms of aesthetics and functionality were measured through Visual Analogue Scale (VAS) scoring system. The VAS system consisted of six different questions put to the patient in the form of a questionnaire regarding the shape of the nose and the impact that it had on his physical, emotional and social life. The score was calculated preoperatively and six months postoperatively in all patients. The minimum follow-up for each patient was six months. Data was analyzed using SPSS. Results: Ten male patients between 14-33 years (25.5 mean SD ± 6) fulfilled the inclusion criteria. The pre op VAS score ranged between 33.3 and 50 (mean 41.2 SD ± 5). The post op VAS score ranged between 70.8 and 87.5 (mean 78.3 SD ± 6.2). There was a statistically significant improvement in the VAS score. Post op recovery was uneventful in all patients. One patient had post op recipient site infection which settled with IV antibiotics. One patient had severe post op donor site pain which was relieved by IV analgesics. Conclusion: Saddle nose is a difficult problem in nasal reconstruction, causing significant psychological and functional problems for the patient. Reconstruction with 9th costal cartilage graft provides functional and psychological relief.